Three axis deviation analysis of CNC milling machine - Subagio, Dalmasius Ganjar; Subekti, Ridwan Arief; Saputra, Hendri Maja; Rajani, Ahmad; Sanjaya, Kadek Heri (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2019)
The manufacturing technology has developed rapidly, especially those intended to improve the precision. Consequently, increasing precision requires greater technical capabilities in the field of measurement. A prototype of a 3-axis CNC milling machine has been designed and developed in the Research Centre for Electrical Power and Mechatronics, Indonesian Institute of Sciences (RCEPM-LIPI). The CNC milling machine is driven by a 0.4 kW servo motor with a spindle rotation of 12,000 rpm. This study aims to measure the precision of the CNC milling machine by carrying out the measurement process. It is expected that the CNC milling machine will be able toperform in an optimum precision during the manufacturing process. Accuracy level testing is done by measuring the deviations on the three axes namely X-axis, Y-axis, and Z-axis, as well as the flatness using a dial indicator and parallel plates. The measurement results show the deviation on the X-axis by 0.033 mm, the Y-axis by 0.102 mm, the Z-axis by 0.063 mm, and the flatness of the table by 0.096 mm, respectively. It is confirmed that the deviation value is within the tolerance standard limits set by ISO 2768 standard. However, the calibration is required for this CNC milling machine to achieve more accurate precision. Furthermore, the design improvement of CNC milling machine and the application of information technology in accordance with Industry 4.0 concept will enhance the precision and realibility.